2015
DOI: 10.1002/aur.1456
|View full text |Cite
|
Sign up to set email alerts
|

T‐Brain‐1 – A Potential Master Regulator in Autism Spectrum Disorders

Abstract: T-Brain-1 (TBR1), a causative gene in autism spectrum disorders (ASDs), encodes a brain-specific T-box transcription factor. It is therefore possible that TBR1 controls the expression of other autism risk factors. The downstream genes of TBR1 have been identified using microarray and promoter analyses. In this study, we annotated individual genes downstream of TBR1 and investigated any associations with ASDs through extensive literature searches. Of 124 TBR1 target genes, 23 were reported to be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 75 publications
(111 reference statements)
0
50
0
Order By: Relevance
“…TBR1's role as a master regulator of cortical development has long made it a candidate regulator of ASD genes (Bedogni et al 2010;Chuang et al 2015); here, we measure its binding genomewide in the developing cortex and confirm its role in regulating other high-confidence ASD genes for the first time. The enrichment of TBR1 ChIP-seq peaks adjacent to high-confidence ASD genes suggests that TBR1 can be used to select a subset of probable ASD genes that are less tolerant to LoF alleles and could be more relevant to ASD (Table 3).…”
Section: Tbr1 Regulates Autism Risk Genesmentioning
confidence: 66%
“…TBR1's role as a master regulator of cortical development has long made it a candidate regulator of ASD genes (Bedogni et al 2010;Chuang et al 2015); here, we measure its binding genomewide in the developing cortex and confirm its role in regulating other high-confidence ASD genes for the first time. The enrichment of TBR1 ChIP-seq peaks adjacent to high-confidence ASD genes suggests that TBR1 can be used to select a subset of probable ASD genes that are less tolerant to LoF alleles and could be more relevant to ASD (Table 3).…”
Section: Tbr1 Regulates Autism Risk Genesmentioning
confidence: 66%
“…Considering that NFI proteins have recently been implicated in diseases such as autism and cancer (Chuang, Huang, & Hsueh, ; Fancy, Glasgow, Finley, Rowitch, & Deneen, ; Genovesi et al, ; Glasgow et al, ; Ho et al, ; Idbaih et al, ; Lacroix et al, ; Lastowska et al, ; Le‐Niculescu et al, ; Lee et al, ; Song et al, ; Stringer et al, ; Suwarnalata et al, ; Tsang et al, ; Vyazunova et al, ), a thorough analysis of their expression in the adult brain is required. Here, we examined both region and cell‐type‐specific expression in the adult mouse cerebral cortex using antibodies specific for NFIA, NFIB, and NFIX.…”
Section: Introductionmentioning
confidence: 99%
“…25 Human genetic studies have indicated that TBR1 is a high-confidence risk factor for ASD and intellectual disability. [26][27][28][29][30][31] Because interaction with CASK increases the transcriptional activity of TBR1 to upregulate Grin2b expression, 14,24,[32][33][34] the TBR1-GRIN2B pathway is likely involved in the function of CASK in regulating intellectual ability. Our previous study showed that the Thr724 (T724) residue of rat CASK protein is the protein kinase A (PKA) phosphorylation site.…”
Section: Introductionmentioning
confidence: 99%